The Addition Of Pressure Biofeedback Unit In Forward Head Exercise Is Better On Improving Neck Alignment Asymptomatic Forward Head Posture - I Gede Eka Juli Prasana; I Nyoman Adi Putra; Wahyuddin; I Ketut Suyasa; Muliarta; I Made Krisna Dinata (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Asymptomatic forward head posture is a chronic condition without symptoms. Improvement in neck alignment can be enhanced by adding a pressure biofeedback unit to forward head exercises. The aim of this study was to determine if the addition of a pressure biofeedback unit to forward head exercises is more effective in improving neck alignment in high school students with asymptomatic forward head posture compared to forward head exercises alone. This study was conducted at SMA N 1 Semarapura in April-May 2021, using a two-group pre-post test design with simple random sampling. There were two groups consisting of 14 samples each. Group I was given forward head exercises with the addition of a pressure biofeedback unit, and Group II was given forward head exercises alone. The outcome measure for neck alignment was the craniovertebral angle, measured using a goniometer. Analysis was performed using the Shapiro-Wilk test and Levene's test. The difference in mean neck alignment was tested using paired t-tests. An independent sample t-test showed an increased difference in neck alignment in both groups. In Group I, the mean pre-test score was 45.57±1.45 and the post-test neck alignment was 53.21±1.36, with a mean difference of 7.35±1.49 and a p-value of 0.000. In Group II, the pre-test score was 45.78±1.85 and the post-test score was 50.28±1.22, with a mean difference of 4.5±1.2 and a p-value of 0.000. A significant difference in neck alignment improvement was found based on the comparison test, with a p-value of 0.000. The study results indicate a significant difference in the improvement of neck alignment between the two groups. The addition of a pressure biofeedback unit to forward head exercises is effective in improving neck alignment in high school students with asymptomatic forward head posture at SMA N 1 Semarapura.